Stereotipy neobuctroennosti i necivilizovannosti Poccii v tekstah CMI - Majdanova, Lûdmila M. (Stylistyka, 2021)
This article considers two Russian social consciousness stereotypes interpreted in the press of 199 1 -2004 applying the ideas of men tal linguistics. These are the stereotypes of inconvenienced and non-civilized Russia. During the initial period of Russian new press development the stereotypes are functioning within the contexts attributing them now to the USSR now to Russia. The time and modality of the statements are not fixed. What they imply may be generally stated as follows: "the inconvenienced and non-civilized USSR should be replaced by well-balanced and civilized Russia". However, these stereotypes do not disappear with the development of the press. By contrast, they tum into the transparent motives of the discourse which has something in common with the evaluation ofRussia in XVII-XIX centuries. The stereotype ofbeing inconvenienced always appears in the texts as a crash or crisis of different social spheres. The meaning of it is expressed in a number of words used both in the terminological and non-terminological way, in the literał sense of a w ord and metaphorically. The meaning of the w ord "crash" is realized in severa! standard contexts. The context of "the crash of hopes" represents "crash" as an unexpected consequence of the situation which was to be successful. According to the materiał this motif is repeatedly addressed to year after year. The context of "those who are to blame for the crash" manifests itself in two ways depending on who is to blame. An inner or outer "enemy" may be named. This context gives mass consciousness the formulations describing the situation in the country in a precise way: "the bureaucracy against people struggle", "the West is robbing Russia". This characteristic quality of the West influences the evaluation of the "non-civilized" notion. There appear negative evaluations of the civilized West and positive evaluations of non-civilized Russia. The West in associated with the power of money and the armed thrusting of democratic values. Non-civilized Russia is said to be the keeper of age-o Id national traditions. The revival and constant application of mass consciousness stereotypes of"inconvenienced and non-civilized Russia" contribute to shaping the generał discourse modality of instability which reflects the state of the society solving the problems of its future.